TRANSFORMATIONAL LEADERSHIP, ORGANIZATIONAL CULTURE, AND EMPLOYEE PERFORMANCE: THE MEDIATING ROLE OF WORK MOTIVATION IN INDONESIAN MANUFACTURING FIRMS - Lilis Sulastri; Iman Supratman; Neli Yuliyani; Kadar Nurjaman; Muhammad Aditya Lanika (UIN Sunan Gunung Djati Bandung, 2025)
This study examines the direct and indirect effects of transformational leadership and organizational culture on employee performance, mediated by work motivation, in the context of manufacturing firms in Indonesia. A quantitative, cross-sectional survey design was employed, involving 250 employees from medium- to large-scale manufacturing companies in West Java. Data were analyzed using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) technique. The findings indicate that transformational leadership and organizational culture have significant positive effects on work motivation and employee performance. Moreover, work motivation mediates the relationship between both independent variables and employee performance. This research contributes to the existing literature by integrating leadership and organizational culture perspectives into a single model mediated by motivation, particularly in a developing country context. The practical implication of this study is that manufacturing firms should invest in leadership development programs and foster a supportive culture to enhance employee performance through improved motivation.